2007
DOI: 10.1002/j.2168-9830.2007.tb00915.x
|View full text |Cite
|
Sign up to set email alerts
|

First Steps in Understanding Engineering Students' Growth of Conceptual and Procedural Knowledge in an Interactive Learning Context

Abstract: The development of procedural knowledge in students, i.e., the ability to effectively solve domain problems, is the goal of many instructional initiatives in engineering education. The present study examined learning in a rich learning environment in which students read text, listened to narrations, interacted with simulations, and solved problems using instructional software for thermodynamics. Twenty‐three engineering and science majors who had not taken a thermodynamics course provided verbal protocol data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 18 publications
3
48
0
Order By: Relevance
“…8 While some shallow learning is necessary, for example to learn discipline-specific terminology, most educators strive to achieve deep learning in their classrooms. Study results are mixed learning gains associated with use of technology, with some reporting shallow learning gains 9 and others resulting in deeper learning. [10][11][12][13] Technology implementation through simulations or virtual experiments give students experiences at little cost (other than computing facilities), increased flexibility (can be completed outside of class), and greater breadth (some experiences are not feasible unless simulated).…”
Section: Is the Answer Reasonable Or Ridiculous? Common Factors Amongmentioning
confidence: 90%
“…8 While some shallow learning is necessary, for example to learn discipline-specific terminology, most educators strive to achieve deep learning in their classrooms. Study results are mixed learning gains associated with use of technology, with some reporting shallow learning gains 9 and others resulting in deeper learning. [10][11][12][13] Technology implementation through simulations or virtual experiments give students experiences at little cost (other than computing facilities), increased flexibility (can be completed outside of class), and greater breadth (some experiences are not feasible unless simulated).…”
Section: Is the Answer Reasonable Or Ridiculous? Common Factors Amongmentioning
confidence: 90%
“…First described by Marton and Säljö, 8 deep learning occurs when students try to understand the material while shallow learning occurs when students simply memorize the material. Some studies have found that including instructional software emphasized lower-level cognitive processes, 9 but a larger number report learning gains when implementing technology in the classroom through virtual experiments or online instruction. [10][11][12][13] Additionally, incorporating simulations into the classroom can increase visualization and problem-solving processes, 14,15 as well as show positive gains in student selfefficacy with respect to engineering skills.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding how to actualize these alternative ways of thinking and innovative mindsets in students' engineering identity development is key to creating engineers that fit with the National Academy of Engineering's vision for the Engineer of 2020 4 and developing diversity in thoughts and innovation. A recent focus in engineering education on cognitive diversity has highlighted some aspects of latent diversity [24][25][26][27][28][29] (e.g., ways of thinking and problem solving) but not others (e.g., motivation or epistemology).…”
Section: Relevant Literaturementioning
confidence: 99%
“…Understanding how to actualize these alternative ways of thinking and innovative mindsets in students' engineering identity development is key to creating engineers that fit with the National Academy of Engineering's vision for the Engineer of 2020 4 and developing diversity in thoughts and innovation. A recent focus in engineering education on cognitive diversity has highlighted some aspects of latent diversity [24][25][26][27][28][29] (e.g., ways of thinking and problem solving) but not others (e.g., motivation or epistemology).In the following sections, I explore the some of the current engineering education literature around particular theoretical constructs commonly used to understand how students navigate their engineering pathways. I focus on a starting set of attitudes, mindsets, and beliefs that are widely researched and often used in understanding diverse students' pathways from a demographic standpoint.…”
mentioning
confidence: 99%